PENGEMBANGAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN BERMAIN EDUKATIF - Fitriani; Jamri (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2024)
Creativity is one of the fundamental potentials that needs to be nurtured from early childhood because it contributes significantly to a child's ability to think flexibly, generate original ideas, and solve problems throughout life. Educative play activities, which combine the pleasure of play with a deliberate educational purpose, are considered an effective means of stimulating children's creativity because play naturally provides children with the freedom to explore, imagine, and experiment without fear of failure. This article aims to examine the concept of creativity and educative play, to describe various forms of educative play activities that can stimulate early childhood creativity, and to analyze the supporting and inhibiting factors in developing creativity through play. This study uses a qualitative approach with a literature review (library research) method, collecting, analyzing, and synthesizing relevant books, national and international journal articles, and government guidelines related to creativity and educative play in early childhood education. The results show that various forms of educative play, such as constructive play using building blocks, art and craft activities, role play, movement and song activities, and play using educative game tools (Alat Permainan Edukatif/APE), are able to stimulate the main dimensions of creativity, namely fluency, flexibility, originality, and elaboration. The role of teachers as facilitators who provide open-ended activities, sufficient time, and a supportive environment, together with the availability of varied and safe play tools, are key factors in optimizing children's creative development. This article concludes that educative play activities are an effective and developmentally appropriate strategy for developing early childhood creativity when designed intentionally and supported by a conducive learning environment.